(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
The alienation of the most challenging human phenomena, especially in our time, and those who fear its effects and reflections and who considers it a concept that may have the meanings of inevitability and coercion as a human behavior is inevitable, tarnish concepts and ideas and may indeed be a challenge on the levels of knowledge and abstract and realistic The concept of alienation between the two dimensions of general abstract knowledge or the so-called epistemological dimension and social dimension. Or knowledge related to the field of sociology, which is more discussion and treatment being a concept of epistemological sociological at the same time. Keywords- Alienation, epistemological analysis, sociological analysis, educational alienation, Family alienation, political alienation